Genomic relatedness and clinical significance of Streptococcus mitis strains isolated from the urogenital tract of sexual partners. Issue 3 (25th March 2021) - Mores, Carine R.; Price, Travis K.; Wolff, Birte; Halverson, Thomas; Limeira, Roberto; Brubaker, Linda; Mueller, Elizabeth R.; Putonti, Catherine; Wolfe, Alan J.
Abstract : Research into the lower urinary tract (LUT) microbiota has primarily focused on its relationship to LUT symptoms (LUTS), taking snapshots of these communities in individuals with and without LUTS. While certain bacterial taxa have been associated with LUTS, or the lack thereof, the temporal dynamics of this community were largely unknown. Recently, we conducted a longitudinal study and found that vaginal intercourse resulted in a shift in species richness and diversity within the LUT microbiota. This is particularly relevant as frequent vaginal intercourse is a major risk factor for urinary tract infection (UTI) in premenopausal women (Aydin et al. Int Urogynecol J 2015;26:795–804). To further investigate the relationship between vaginal intercourse and LUT microbiota, here we present the results of a 3 week study in which daily urogenital specimens were collected from a female participant and her male sexual partner. Consistent with our previous findings, the LUT microbiota changed after vaginal intercourse, most notably a high abundance of Streptococcus mitis was observed post-coitus. We isolated and sequenced S. mitis from both sexual partners finding that: (i) the S. mitis isolates from the female partner's urogenital tract were genomically similar throughout the duration of the study, and (ii) they were related to one isolate from the male partner's oral cavity collected at the end of the study, suggesting transmission between the two individuals. We hypothesize that blooms in S. mitis after vaginal intercourse may play a role in coitus-related UTI. We found that a S. mitis isolate, in contrast to a Lactobacillus jensenii isolate displaced after vaginal intercourse, cannot inhibit the growth of uropathogenic Escherichia coli . Thus, this bloom in S. mitis may provide a window of opportunity for a uropathogen to colonize the LUT.